Interview with Glenn Seaborg (1988)
Raw footage of an interview with Glenn Seaborg about the periodic table and his discovery of new transuranium elements. The interview is conducted by two different unidentified men. This tape is a "window dub" of raw footage, with the running time displayed over the image. The interview is frequently interrupted by what appears to be the sound of airplanes passing overhead. Footage from this conversation was used in the periodic table episode of the television show World of Chemistry, hosted by Roald Hoffman. Approximately the last five minutes of the tape contain a demonstration of an unidentified gas in a Crookes Tube (an electrically charged cathode ray tube) reacting to a magnet.
Keywords: Seaborg, Glenn T. (Glenn Theodore), 1912-1999; Transuranium elements; Periodic table of the elements